Excerpts from the history of food safety - Szeitzné Szabó Mária (Élelmiszervizsgálati közlemények, 2016)
Just as obtaining and consuming food is part of everyday human life, so have foodborne diseases been occurring regularly throughout history. Most of these sank into oblivion, however, certain events of greater importance, or ones that affected a large number of people or were memorable because of their nature, novelty or long-term effects have been included in source materials preserving our history in written form. There are references to diseases in the holy books that constitute the basis for certain religions (e.g., the Bible or the Quran), as well as detailed food preparation and eating rules aimed at preventing diseases. Because of the rudimentary nature of scientific knowledge, sometimes it took several centuries until the cause of an epidemic disease could be determined and the measures necessary for prevention could be taken. These diseases were often outbreaks of microbial origin, but toxicoses also occurred frequently, and in many cases they had serious, long-term consequences. This paper mentions several such events, for example, chronic lead poisoning that presumably played a role in the fall of the Roman Empire, or mass diseases accompanied by different syndromes caused by mold toxins. Unfortunately, this phenomenon was not eliminated by the development of science and technology, so foodborne illnesses still occur and, because of globalization and world trade, they can reach practically any part of the world in a short time. The article also discusses the risks of industrial development and also some of the major food counterfeiting cases that occurred recently and which lead to mass diseases.